From coins to cancer therapy: Gold, silver and copper complexes targeting human topoisomerases. Issue 3 (1st February 2020) - Ceramella, Jessica; Mariconda, Annaluisa; Iacopetta, Domenico; Saturnino, Carmela; Barbarossa, Alexia; Caruso, Anna; Rosano, Camillo; Sinicropi, Maria Stefania; Longo, Pasquale
Graphical abstract: Abstract: Cancer is a complex issue and, even though the prevention basics and therapy have been implemented, it is still the second leading death cause worldwide. With the hope to discover new powerful and safer molecules to fight cancer, many researchers focused their attention on metal-based compounds, starting from the most famous and successfully employed anticancer drug, i.e. cisplatin. The current article aims to report the most recent discoveries about the use of gold, silver and copper complexes as antitumor agents, highlighting their influences on important enzymes, namely human topoisomerases. The latter are fundamental for the cell life and, if overexpressed, strongly implicated in cancer onset and progression. The identification of lead complexes targeting human topoisomerases and gifted with the appropriate chemical and pharmacological properties represents a fecund starting point to obtain new and more effective anticancer molecules.